The Style of Decision: Consumer Wisdom and the mediating role of the Heuristic-Systematic Model of Information Processing in Clothes Shopping - Sakr, Nourane (AUC Knowledge Fountain, 2026)
Rationality and emotions are often treated as opposing forces in decision-making. Yet what if the more productive question is not which one prevails, but how a balance between the two might be achieved? Wisdom offers precisely this kind of integrative paradigm. Wisdom is a central trait for self-development; yet, little has been explored on Consumer Wisdom from a communications perspective. The theory has been initially examining ecology principles with an extensive space in consumer behavior and marketing practices. This research approaches consumer wisdom in online fashion advertising context whilst understanding the common information processing modes; evoked by the mediation of the Heuristic-Systematic model (HSM). Quantitative research was applied using an online survey. The questionnaire was conducted with 299 millennials and Gen Z respondents as considered the highliest digital users, asking them about their personal lifestyle, shopping experiences and the effect of online clothing ads on their purchase intention. Results indicated that consumer wisdom, fashion clothing involvement and purchase intention all entail the concurrent processing of heuristic and systematic cognitions. Consumer wisdom has a stronger effect on the systematic mode versus heuristic, while the consumer fashion involvement had a more dominant effect on the heuristic mode versus the systematic. The heuristic and the systematic were both significant in purchase intention. The presented study contributes to Consumer Wisdom theory and consumer fashion clothing involvement, as the first to tackle dual information processing in marketing communication, inviting more multi-disciplinary scholarly research.